2015
DOI: 10.1007/s10853-015-9660-2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of structural and textural parameters of carbon nanofibers on their capacitive behavior

Abstract: Herringbone, platelet, and tubular carbon nanofibers (CNFs) were synthesized by catalytic chemical vapor deposition using methane, propane, and ethylene as carbon precursors. Alumina-supported nickel and iron catalysts were used for the syntheses. The resultant CNFs were characterized by scanning electron microscopy, transmission electron microscopy, and nitrogen sorption at 77 K. The performance of a CNF-based supercapacitor working in 6 mol L -1 KOH was analyzed using cyclic voltammetry, galvanostatic charge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…[ 6 ] To date, the most commonly researched MXene is titanium carbide (Ti 3 C 2 T x , where T x define surface terminations, such as OH, F, and O), which showed much higher C sp than previously reported electrode materials such as porous carbons, [ 7 ] CNT, [ 8 ] graphene, [ 9 ] CNFs. [ 10 ] In addition, our previous research has been demonstrated that Ti 3 C 2 produced via HF etching and subsequent delamination with tetrabutylammonium hydroxide (TBAOH) shows enhanced capacitive behavior. [ 11 ] Furthermore, transitional metal dichalcogenides and particularly tungsten sulphide (WS 2 ) reveals enhanced electrical and [ 12 ] thermal properties, [ 13 ] shorter ions transfer pathway (compared to bulk materials), [ 14 ] metallicity in nature, [ 15 ] and yield when employed as FSC electrode materials.…”
Section: Introductionmentioning
confidence: 99%
“…[ 6 ] To date, the most commonly researched MXene is titanium carbide (Ti 3 C 2 T x , where T x define surface terminations, such as OH, F, and O), which showed much higher C sp than previously reported electrode materials such as porous carbons, [ 7 ] CNT, [ 8 ] graphene, [ 9 ] CNFs. [ 10 ] In addition, our previous research has been demonstrated that Ti 3 C 2 produced via HF etching and subsequent delamination with tetrabutylammonium hydroxide (TBAOH) shows enhanced capacitive behavior. [ 11 ] Furthermore, transitional metal dichalcogenides and particularly tungsten sulphide (WS 2 ) reveals enhanced electrical and [ 12 ] thermal properties, [ 13 ] shorter ions transfer pathway (compared to bulk materials), [ 14 ] metallicity in nature, [ 15 ] and yield when employed as FSC electrode materials.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the pore size of ACMs decreases from 7.71 nm (ACM-1) to 5.34 nm (ACM-2) when the PHHC precursor changes from C 2 Cl 6 to C 6 Br 6 . These results illustrate that the rigid brace effect of benzene rings and the placeholder effect of large size halogens facilitate the formation of the developed pore structure, which is beneficial to their application in supercapacitors [36,37]. As shown in Fig.…”
Section: Characterizations Of Acmsmentioning
confidence: 63%
“…Two samples of CNTs were made: dried (CNT) and calcined at 450°С (CNT450). "Among the studied CNFs, the highest capacitance value was obtained for the platelet-type CNFs; tubular CNFs exhibited the lowest capacitance value" [16]. The average values of pore diameter Dav (Table 1) were calculated by us as arithmetic mean of the diameters of the DpTEM interval measured by the uthors using the TEM method [16].…”
Section: Range Of Pore Shapesmentioning
confidence: 99%